Neighborhood paradiplomacy in Chile: thought and practice of non-state foreign policy - Raúl Bernal-Meza (Revista Brasileira de Política Internacional)
Abstract The text analyzes Chilean neighborhood paradiplomacy with Peru, Bolivia and Argentina, practice carried out under three conditions: a history of conflicts and border problems with the three neighbors; the absence of diplomatic relations between Chile and Bolivia and the existence of subnational and social actors paradiplomacy, restricted by the power of the State, whose vision is dominated by security perceptions.